Coaching executivo no Brasil: desenvolvimento humano ou econômico? - Mauro Rodrigo Schneider (2022)
This dissertation aimed to investigate the practice of coaching in Brazil, especially the executive coaching. In order to attain this objective, two phenomena were researched that are linked to the central theme: neoliberalism and the culture of management. A socioeconomic and historical study was developed – both regarding national and international scopes – to support the discussions and results presented. Regarding the methodological approach, this research used content analysis (BARDIN, 2011) in two moments: firstly, in the creation of categories from the national scientific production on the subject and, consequently, in the evaluation of two of the most relevant coaching schools in Brazil, as well as its multimedia courses and also interviews with its creators who sought to answer the following question: “Executive coaching in Brazil: human or economic development?” The results pointed to human development, but within the standards of neoliberalism, that is, through instrumental rationality structured by the current economic paradigm. In addition, the relationship between neoliberalism, management culture and the practice of coaching as elements that feed back into the social fabric was confirmed.